State ownership and the risk‐reducing effect of corporate derivative use: Evidence from China. (2nd January 2021) - Guo, Huimin; Pan, Zheyao; Tian, Gary Gang
Abstract: Using hand‐collected derivative use data on publicly listed firms in China, we document that derivative use has a significant risk‐reducing effect, but this effect is 40% weaker in state‐owned enterprises (SOEs) than in non‐SOEs. We also find that soft‐budget constraints and information transmission inefficiency are two mechanisms through which state ownership impedes this risk reduction. First, financial distress reduces the impact of the soft‐budget constraints, mitigating the weaker risk‐reducing effect of state control. Second, the risk‐reducing effect of derivative use is weaker in local SOEs than in central SOEs, as the former are subject to more information frictions than the latter. Our paper provides new information and insight into risk management effectiveness from the perspective of ownership identity.